77 W high beam quality Nd:YVO4 Innoslab amplifier. (29th October 2015) - Zhang, Xin; Zhang, Hengli; Mao, Yefei; Sang, Sihan; Zou, Junyu; Xing, Jichuan; Xin, Jianguo; Jiang, Yi
Abstract: We reported a compact and efficient Nd:YVO4 partially end-pumped slab (Innoslab) nanosecond amplifier. The power of the seed was 5 W at a pulse repetition rate of 30 kHz with beam quality factors of M 2 < 1.3. A plane–plane cavity was used in the amplifier for high efficiency. With effective shaping of the seed laser, the output of 77 W was obtained under the pump power of 378 W without self-excitation. The optical to optical conversion efficiency was 23.8%, and the beam quality factors of M 2 were 1.52 and 1.32 in the horizontal direction and in the vertical direction, respectively.